Lack of Collections as Data: Making Meaning out of the Films We Cannot See - Smith, Christine (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
Streaming media licensing by academic libraries has, in recent decades, grown in breadth and complexity. Simultaneously, in the communication and media studies community, critical analysis of consumer-direct streaming media or over-the-top (OTT) platforms has explored media ownership and power dynamics. This article intends to bridge the gap between these two worlds and reframe the discourse of research into modern library analysis, turning away from the “how” media gatekeeping is being experienced by academic librarians and towards “what” media is being withheld. The analysis will be done through a case study of a collection, or rather, absence of collection, of films requested but unavailable for institutional licensing in a specific Canadian academic library. In exploring request, film, and market availability data for each title and analyzing trends found therewithin, the article aims to bring to light possible implications to the future of academia as technological advancements and media powerholders render certain audiovisual cultural artifacts inaccessible.